2017
DOI: 10.5222/terh.2017.186
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum fatigue, self-care power of women and related factors

Abstract: ÖZAmaç: Araştırmanın amacı, kadınların doğum sonrası ikinci ayında görülen yorgunluk düzeyi, özbakım gücü, yorgunluk ile özbakım gücü arasındaki ilişki ve ilişkili faktörleri belirlemektir. Yöntem: Araştırma analitik-kesitsel olarak gelişigüzel örnekleme yöntemi ile belirlenen 313 doğum sonrası kadın ile yapılmıştır. Araştırmanın verileri kadınların tanıtıcı ve bağımsız değiş-kenlerinin sorgulandığı soru formudur. Yorgunluk İçin Görsel Benzerlik Skalası, Özbakım Gücü Ölçeği, Edinburgh Doğum Sonrası Depresyon Ö… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…According to the results of studies conducted so far, selfcare agency has been reported to be high among working women (6,12,14). In our study, self-care agency was found to be higher among women working as civil servants or those working in the education sector.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…According to the results of studies conducted so far, selfcare agency has been reported to be high among working women (6,12,14). In our study, self-care agency was found to be higher among women working as civil servants or those working in the education sector.…”
Section: Discussionsupporting
confidence: 58%
“…While some studies indicated that self-care agency increased in parallel to the increase in the level of education (12), others showed that the level of education had no effect or did not increase the self-care agency (1,13,14).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study showed that the self‐care agency mean scores of pregnant women with two or more children younger than 6 years were lower. There are studies indicating that the self‐care agency mean scores decrease as the number of children increases (Aktaş & Karaçam, 2017 ; Çelik Sis & Derya Aksoy, 2019 ; Şanlı & Öncel, 2014 ). This study had shown that those who have two or more children younger than 6 years had a high caregiver burden mean score.…”
Section: Discussionmentioning
confidence: 99%
“…Alleviating labor and postpartum fatigue positively affects postpartum comfort and satisfaction of women. In addition, qualified midwifery and nursing care/ support services increase their physical/social comfort and childbirth satisfaction (8).…”
Section: Introductionmentioning
confidence: 99%